Investigation of the applicability of the microwave image to complement the optical image for the preparation of a coastal configuration map (Research in Agriculture Livestock and Fisheries, 2024)
The coastal area, being the transition zone between the sea and land, is a country's most diverse and dynamic zone in terms of its environment and economy. A variety of economic activities revolve around this region. Mapping the dynamic coastal configuration is an essential tool for sustainable coastal zone management. Satellite remote sensing offers excellent resources for monitoring and mapping coastal zones. Microwave remote sensing images, in tandem with optical remote sensing imagery, can be used for mapping coastal configurations. However, both images have some limitations. In this context, the present article explores the integrated use of microwave images to supplement optical images to overcome these limitations and generate a coastline configuration map.Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 47-51